Emergency and Trauma of the Pelvic Ring - Leone, Antonio; Cassar-Pullicino, Victor N.; Pérez, Miguel Herrera; Guglielmi, Giuseppe (Seminars in Musculoskeletal Radiology, 2017)
Pelvic ring fractures are a common consequence of high-energy blunt trauma with a high rate of morbidity and mortality due to associated injuries, especially to the head, pelvic viscera, and vascular structures. The Young and Burgess classification system is the most widely utilized for categorizing pelvic ring injuries and assessing stability. The initial identification of these injuries often comes from an anteroposterior radiograph; however, computed tomography examination with three-dimensional volume-rendered reconstructions represents the reference standard and has essentially eliminated the requirement for inlet and outlet views. The appropriate treatment depends on a good knowledge of the anatomy and biomechanics of the pelvis. This review article underlines the importance of the integrity of ligaments to pelvic stability and describes the patterns of pelvic ring injuries and their associated mechanisms of injury.
Keywords: pelvic ring; pelvic ring fractures; pelvic ring radiography; pelvic ring computed tomography